The Influence Of Work Conflict And Work Spirit On Employee Performance At The Office Of North Galesong District, Takalar Regency - Yusrayanto Yusrayanto; Asriati Asriati; M. Hidayat (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of work conflict and work morale on employee performance at the North Galesong District Office, Takala Regency. This research method is descriptive quantitative using simple regression analysis. Research data was obtained from respondents through a questionnaire with 32 employees as respondents. Statistical analysis was carried out using the SPSS 20 program. The research results obtained by the author of the work conflict variable (????1) and employee performance variable (Y) show that the significant value is 0.310 (>0.05). Obtained t table of 2.048 with a t count of 1.035 then (1.035<2.048) with a significant value (0.310>0.05) then it can be concluded that Ho is accepted and Ha is rejected, meaning that the partial (individual) work conflict variable has no significant effect on employee performance and The partial test (t) of the work enthusiasm variable (????2) on employee performance (Y) shows a significant value of 0.015 (<0.05). Obtained a t table of 2.048 with a calculated t of 2.616 so (2.616>2.048) is significant (0.015<0.05) then it can be concluded that Ho is rejected and Ha is accepted, meaning that the partial (individual) workload variable has a significant effect on employee performance. The tcount value is positive, meaning that the influence that occurs is positive, or can be interpreted as decreasing the workload, which will increase employee performance